Reduced expression of dopamine D2 receptors on astrocytes in R6/1 HD mice and HD post-mortem tissue. (10th January 2022) - Harris, Kate L.; Mason, Sarah L.; Vallin, Benjamin; Barker, Roger A.
Highlights: Astrogliosis is seen in the human post mortem hippocampus. Astrocytes in human HD hippocampus have reduced D2 receptor expression. Astrocytes in R6/1 mouse striatum and hippocampus have reduced D2 receptor expression. Abstract: Dysfunction of the central dopaminergic system is thought to contribute to some of the clinical features of Huntington's disease (HD), and dopamine (DA) receptor antagonists are commonly used to good effect in its treatment. It is well established that there is an early significant reduction in neuronal D2 receptors in HD, considered to be a compensatory response to increased dopaminergic activity. However, no studies have examined the expression of D2 receptors on astrocytes which is important given that these cells have been shown to play a role in the pathogenesis of HD, as well as express dopamine receptors and modulate DA homeostasis in the normal brain. We therefore sought to investigate the expression of D2 receptors on astrocytes in HD, and found them to be reduced in both the R6/1 HD mouse model, and in human post-mortem brain in comparison to controls, suggesting that astrocytes may be important in DA-dependent aspects of HD. Further studies are needed to determine the functional significance of this finding.